ANÁLISE HIDRODINÂMICA NUMÉRICA DE CUPONS EM VASOS AGITADOS MECANICAMENTE - Borges Junior, Donizette (2021)
Onshore hydrocarbon sources are becoming increasingly scarce and, with that, easily accessible reserves, increasingly challenging solutions and technologies. Among the intrinsic challenges to production in this type of reserves, inorganic incrustation stands out as the biggest one. Laboratory-scale stirred tanks with rotating cages (RC) have been qualified for the study of fouling kinetics. In this work, an agitated vessel with rotating cage and unconventional radial impeller (MQ2021) was proposed, in which we sought to model numerically (CFD) and experimentally the hydrodynamics inside the tank, to map the formation of vortices and the influence on the flow. The experimental test for analysis of the formed vortex was carried out in two manufactured tanks, one in accordance with the ASTM G170 standard and another replica of the original tank, but without a viewing window and without an impeller. for the CFD simulations, they were performed in software ANSYS CFX. 15.0 adopting the k-omega SST model (Shear Stress Transport) as a closure for turbulence and validated with the results of the article by Vera et al. (2017). The viewing windows do not influence the flow, the absence of the impeller impairs the incrustation kinetics. The ASTM G170 tank parameters proposed in this work for the study of scale kinetics.